Éléments qui influencent la dynamique de petits groupes et l'expérience d'apprentissage de stagiaires infirmières - Marjolaine Dionne Merlin; Frances Gallagher; Stéphan Lavoie; Charles Bilodeau
Learning experiences in the clinical setting are essential to nursing students' education. These learning experiences are commonly conducted in small groups of students in a health care setting. In such cases, learning in the clinical setting takes place within the context of the dynamics that prevail within these groups. However, there are no studies that have been identified that provide a picture of small group dynamics. This descriptive interpretive study aims to describe group dynamics as it relates to the learning of nursing students. Semi-structured individual interviews were conducted with 12 nursing students, followed by an initial focus group with nine clinical supervisors and a second with eight ward nurses. Three themes emerged from the thematic analysis : 1) the composition of the group, foundation on which dynamics and learning are constructed, 2) the nature of interactions, central to the relationships between students and their learning, and 3) the external components of the student group, a contribution to the group dynamics and learning. This exploratory study allows for a more integrative evaluation of the factors that influence the learning experience of nursing students.